2015
DOI: 10.1039/c5ra15920b
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of icephobic properties based on UV-curable fluorosilicone copolymer films

Abstract: UV-curable fluorosilicone triblock methacrylate copolymer films were prepared for icephobic applications. Water droplets could rebound from the film surfaces at −15 °C due to their high receding contact angles, avoiding ice accretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Ice adhesion strength, which was denominated as ice shear strength in this study to evaluate the horizontal shear strength of ice detaching from the coating surfaces it adhered to, was measured using a custom-built apparatus according to our previous reports. ,, Typically, a stainless steel sheet with the as-prepared coating was placed onto the Peltier plate, on which a hollow glass cylinder (inner diameter of 9.84 mm) hydrophobically treated with 1 H ,1 H ,2 H ,2 H -perfluorooctyl trichlorosilane was placed. Then, 450 μL of deionized water was pipetted in the cylinder, and left in a chamber with a stream of dry N 2 at a temperature of −15 °C for more than 3 h to ensure its total freezing that adhered to the coating surface.…”
Section: Methodsmentioning
confidence: 99%
“…Ice adhesion strength, which was denominated as ice shear strength in this study to evaluate the horizontal shear strength of ice detaching from the coating surfaces it adhered to, was measured using a custom-built apparatus according to our previous reports. ,, Typically, a stainless steel sheet with the as-prepared coating was placed onto the Peltier plate, on which a hollow glass cylinder (inner diameter of 9.84 mm) hydrophobically treated with 1 H ,1 H ,2 H ,2 H -perfluorooctyl trichlorosilane was placed. Then, 450 μL of deionized water was pipetted in the cylinder, and left in a chamber with a stream of dry N 2 at a temperature of −15 °C for more than 3 h to ensure its total freezing that adhered to the coating surface.…”
Section: Methodsmentioning
confidence: 99%
“…Li et al developed a UV-curable films composed of thiol-terminated fluorosilicone methacrylate triblock copolymer, thiol-functionalized PDMS and octavinyl-polyhedral oligomeric silsesquioxanes. The perfluoroalkyl side group presented in crystalline structure and endowed coating with higher hydrophobicity and low ice adhesion . The results showed that ice shear strength was reduced by the synergistic effect of the fluorine and silicone .…”
Section: Active Deicing Strategies To Remove Ice Easier After Freezingmentioning
confidence: 99%
“…The perfluoroalkyl side group presented in crystalline structure and endowed coating with higher hydrophobicity and low ice adhesion. 105 The results showed that ice shear strength was reduced by the synergistic effect of the fluorine and silicone. 106 Surface modification by using fluorine or silicone regents can effectively reduce the ice adhesion strength to about 200− 300 kPa, but the adhesion of ice was too high to remove ice by wind or gravity.…”
Section: ■ Introductionmentioning
confidence: 98%
“…Fluorinated polymers and siloxane polymers are two famous families of materials with extremely low surface energy, outstanding water and oil repellency, excellent thermal and chemical properties, photochemical stability. [6][7][8][9][10][11][12][13][14][15][16][17][18] Fluorosilicone materials, which integrating the advantages of both uorinated polymers and silicone-based polymers, create synergistic effects of uorine and silicon. 7 The synergistic effects of uorine and silicon can improve the comprehensive performance of the materials, especially the surface property.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16][17][18] Fluorosilicone materials, which integrating the advantages of both uorinated polymers and silicone-based polymers, create synergistic effects of uorine and silicon. 7 The synergistic effects of uorine and silicon can improve the comprehensive performance of the materials, especially the surface property. Numerous researchers had focused on the preparation and properties of the uoro-silicone containing poly(meth)acrylate.…”
Section: Introductionmentioning
confidence: 99%